Antituberculous Treatment Itself Might Prevent Visual Impairment in Presumed Tuberculosis-Related Uveitis. (2nd January 2020) - Llorenç, Victor; Benejam, Gibet; Mesquida, Marina; Sainz de la Maza, Maite; Molins, Blanca; Alba, Carmen; Pelegrin, Laura; Martínez, Jose Antonio; Adán, Alfredo
ABSTRACT: Purpose : To study the risk factors for visual loss in presumed tuberculosis-related uveitis (TRU). Methods : Retrospective observational cohort study of patients with TRU, either treated or not for tuberculosis, from January 2005 to January 2017. Clinical and demographic variables were recorded. Main outcome measure was a loss of visual acuity (VA) of ≥2 Snellen lines. A Generalized Estimation Equation was used to control between-eyes bias. A backward stepwise logistic regression multivariate analysis was conducted to elucidate independent risk factors. Results : One hundred and thirty-eight eyes from 82 patients were included. There were 45 males, median age at onset of uveitis was 40 years (Interquartile range, IQR 24). The median follow-up was 36 months (IQR 49.75) and 51 patients completed antituberculous treatment (ATT) for a mean of 9.37 months. In the multivariate model, ATT was the only independent protective factor for loss of VA (OR 0.13, 95% CI 0.04–0.37, p < 0.001). Conclusion : ATT itself may prevent visual loss in TRU.